PELATIHAN METODE AKTIF UNTUK PENINGKATAN KUALITAS PEMBELAJARAN DI SEKOLAH MENENGAH PERTAMA (SMP) PULAU PANJANG TIMUR - Juni Mahanis; Nurhayati; Enik Nurfaizah; Usvim Varadilla; Dina Liana; Mukhammad (Empowerment Journal, 2025)
This training aimed to improve the quality of learning in Junior High Schools (Sekolah Menengah Pertama, SMP) in Pulau Panjang Timur through active learning method training for teachers. The quality of education in remote areas such as Pulau Panjang Timur often faces challenges such as limited access to innovative teaching methods and low student engagement in the learning process. Therefore, training in active learning methods serves as a solution to enhance student participation, improve understanding of subject matter, and strengthen teachers' teaching skills. This research employed a qualitative approach using a case study method involving observations and in-depth interviews with teachers and students who participated in the training. The results show that the active learning method training successfully improved teacher competence. Prior to the training, the teachers’ understanding of digital media was only at 58% (categorized as "adequate"). However, after conducting intensive training and mentoring for three days, the post-training evaluation revealed a significant improvement, reaching 84% (categorized as "good"). Trained teachers were also able to manage classrooms more effectively and implement more creative techniques, supporting a more enjoyable and interactive learning environment. However, the study also identified challenges, particularly the lack of facilities and infrastructure, which affects the full implementation of active methods. Therefore, further support from the government and related stakeholders is needed to improve educational facilities and resources in the region. This research provides a positive contribution to the development of more inclusive and relevant teaching methods for the Pulau Panjang Timur area